2005
DOI: 10.1093/ejo/cji031
|View full text |Cite
|
Sign up to set email alerts
|

Enamel loss at bond-up, debond and clean-up following the use of a conventional light-cured composite and a resin-modified glass polyalkenoate cement

Abstract: The aim of this study was to determine whether there was any difference in the degree of enamel loss at bond-up, debond and enamel clean-up when two different adhesive systems were tested and with four different methods of enamel clean-up. The adhesive systems were 37 per cent o-phosphoric acid with Transbond XT (group 1) and 10 per cent poly(acrylic acid) conditioner with Fuji Ortho LC (group 2). Using flattened enamel specimens, enamel loss at each stage was determined using a planer surfometer. These stages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 19 publications
3
65
0
13
Order By: Relevance
“…Another study reported smaller losses, ranging from 1.1 µm to 4.57 µm (HOSEIN et al, 2004). Despite differences in enamel loss described in the literature depending on acid concentration and/or methodology, studies show agreement that this stage causes greater structural loss (SILVERSTONE, 1974;DIEDRICH, 1981;HOSEIN et al, 2004;IRELAND et al, 2005). Clinically, any orthodontist should minimize the loss of enamel during the etching procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported smaller losses, ranging from 1.1 µm to 4.57 µm (HOSEIN et al, 2004). Despite differences in enamel loss described in the literature depending on acid concentration and/or methodology, studies show agreement that this stage causes greater structural loss (SILVERSTONE, 1974;DIEDRICH, 1981;HOSEIN et al, 2004;IRELAND et al, 2005). Clinically, any orthodontist should minimize the loss of enamel during the etching procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a plethora of studies evaluating the bond strength of different orthodontic adhesives and surface alterations after bracket debonding, 8,9 only a few studies have focused on possible changes in the color of enamel after treatment. In a clinical study, the color values were measured in patients before and after orthodontic treatment, and it was reported that the color of natural teeth changed after orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…12 Greatest enamel loss was seen when ultrasonic scaler was used for adhesive removal 12,27 while diamond finishing burs were extremely injurious as they produce deep grooves on enamel. 5,22 Eminkahyagil N et al 15 concluded that clean-up with high-speed tungsten carbide bur was most hazardous to enamel.…”
Section: Discussionmentioning
confidence: 99%